PERFORMANCE MANAGEMENT MODEL OF BANKING COMPANIES IN INDONESIA - Moh. Nasih (Trunojoyo University of Madura, 2016)
Bank is a financial institution with a function as an intermediary and creates its benefits through withdrawls and lending funds to the community. To obtain optimal profits, banks have to manage any resources and controlled assets. This study aimed to develop and examine the model of performance creation through asset, human cost, equity, intellectual capital and non-financial performance.The study was conducted in the Indonesian banking companies. The data obtained were processed using SEM techniques. The results show that the model developed can be accepted by probability (p) 0,277 (more than 0,05) x2 model 5.100; RMSEA 0,049 (less than 0,08) and GFI 0,985 (more than 0,90). This means that the banking company's financial performance is determined by how it is performing its function as an intermediary institution that is manifested in non-financial performance. In addition, the factor of intellectual capital, assets, human cost and the equity are together is an important determinant of superior performance of the company. As such, those factors should get attention and managed in a healthy, optimal, proportional, and cautious way.